Distinct molecular response patterns of activating STAT3 mutations associate with penetrance of lymphoproliferation and autoimmunity - Jägle, Sabine (Clinical immunology (Orlando, Fla.), 2020)
Copyright © 2019 Elsevier Inc. All rights reserved.